AB0131 NAMPT/VISFATIN in osteoarthritis: An adipokine involved in the communication between cartilage and bone. (23rd January 2014) - Laiguillon, M.-C.; Bougault, C.; Priam, S.; Gosset, M.; Mladenovic, Z.; Pigenet, A.; Jacques, C.; Houard, X.; Berenbaum, F.; Sellam, J.
Abstract : Background: It has been recently demonstrated that a pro-inflammatory adipokine called visfatin can be produced by chondrocytes in osteoarthritis (OA). Visfatin is also known as nicotinamide phosphoribosyltransferase (Nampt), the rate-limiting enzyme in the salvage pathway of nicotinamide adenine dinucleotide (NAD) biosynthesis from nicotinamide. Interestingly, this pathway is involved in cytokine production such as TNFα. Recently, it has been suggested that the pathophysiology of OA may rely, at least in part, on the release of soluble mediators coming from chondrocytes and acting on bone cells. To date, the action of Nampt/visfatin on osteoblasts remains unknown. Objectives: We aimed i) to investigate whether Nampt/visfatin could be responsible for osteoblast activation and ii) assess the role of the enzymatic activity in this osteoblast activation. Methods: Osteoblasts were obtained by enzymatic digestion of calvaria from Swiss mice and cultured for 3 weeks. Cells were then stimulated with a recombinant Nampt/visfatinfor 24 hours. In order to evaluate the part of the enzymatic activity in the cell stimulation, a 4 hours pre-treatment of osteoblasts with APO866 (10nM), a specific competitive inhibitor of Nampt activity, was performed. The effects on IL-6, Kc (i.e. murine IL-8), IL-1β, MCP-1 and SDF-1 expression and on IL-6 and Kc release were assessed by quantitative PCR and enzyme-linked immunosorbent assay (ELISA), respectively. Results: 5 μg/mL Nampt/visfatin (considered as the optimal concentration according to a dose-response experiment) significantly induced the expression of IL-6, Kc/IL-8, IL-1β, MCP-1 and SDF-1 mRNA (n=4) (Table). The release of IL-6 and Kc proteins was also increased by Nampt/visfatin (104 and 142-fold, respectively; n=4). The inhibition of Nampt/visfatinactivity by APO866 decreased this response at mRNA level (up to 73% of inhibition, see Table) as well as at protein level (38±25% and 42±17% of inhibition for IL-6 and Kc proteins release, respectively). APO866 alone had no effect on osteoblasts activation. The effect of Nampt/visfatin was selective since it did not significantly induce VEGF or TGFβ. Conclusions: We demonstrate that Nampt/visfatinactivates osteoblasts partly through its enzymatic activity which is thus involved in the pro-inflammatory cytokine effect of visfatin. This study suggests that Nampt/visfatin could be part of the cytokine network involved in the communication between cartilage and bone in OA. Disclosure of Interest: None Declared